Optimising digital advance care planning implementation in palliative and end-of-life care: a multi-phase mixed-methods national research programme and recommendations - Allsop, Matthew J.; Birtwistle, Jacqueline; Bennett, Michael I.; Bradshaw, Andy; Carder, Paul; Evans, Catherine J.; Foy, Robbie; Heavin, Ciara; Hibbert, Barbara; Martin, Pablo Millares; Relton, Sam D.; Richards, Suzanne H.; et al. (BMC medicine, 2025)
Background Digital advance care planning (DACP) is increasingly used globally for patients with life-limiting conditions to support real-time documentation and the sharing of preferences for care. There has been low engagement with DACP systems, with patients often having information about their care preferences documented late in their illness trajectory or not at all. To optimise implementation, the Optimal Care research programme sought to understand DACP system use from multiple perspectives to guide their development and evaluation. Methods Between 2020 and 2023, our mixed-methods research programme sought an understanding of DACP implementation from multiple perspectives, including (i) national online survey of end-of-life care commissioning leads in England; (ii) online survey of community and hospital-based health and care professionals in two geographical regions; (iii) semi-structured interviews with a sample of survey respondents; (iv) focus groups and interviews with patients with life-limiting illness and their carers and (v) regional and national Theory of Change workshops. Findings were organised by five phases of a conceptual model of DACP generated during the programme and further categorised using the Non-adoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. Results A total of 788 stakeholders participated. Twenty evidence-based recommendations were distilled from data collected across the research programme to guide the implementation of DACP in routine care. Considerations are provided across the five phases of DACP implementation (system design, recognition of clinical need for DACP, documentation processes, health and care professional engagement with DACP and DACP evaluation). Recommendations prioritise a focus on end-user needs and experiences, alongside highlighting the requisite need for DACP systems to support information exchange across settings involved in the care of people with life-limiting conditions. Conclusions As currently designed and implemented, DACP systems may be falling short of their potential and are not working as intended for patients, carers and health and care professionals. The application of the recommendations should ensure consideration of the wider ecosystem in which DACP is being implemented, prioritising end-user experiences. Future research should prioritise developing approaches that target health and care professional DACP system engagement, alongside developing and evaluating patient and carer access to DACP systems.